Apparatus and Test of Accelerated Carbonation in Concrete - Gonen, Tahir; Yazicioglu, Salih (Gazi Univ, 2005)
Created of an artificial environment in which the rate of the relative humidity, the temperature and the CO2 concentration can be controlled should become for accelerated carbonation. In this study an apparatus which will be able to carried out experiment of accelerated carbonation was developed and an example study was carried out to determine useable of this apparatus.
Keywords: Accelerated carbonation test; carbonation; concrete; carbondioxide; durability